2010
DOI: 10.2320/matertrans.m2010191
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical Synthesis of Zeolite A from Metakaolinite in NaOH Solution

Abstract: Sonochemical synthesis of zeolite A has been conducted by ultrasonic irradiation of mixtures of metakaolinite and NaOH solution. The hydrothermal synthesis at conventional synthesis conditions was undertaken to determine the sonochemical reliability. The enhancement of nucleation and crystallization rate of zeolite A was achieved by ultrasound. In the ultrasonic field, zeolite A once formed in the suspension has been converted into hydroxysodalite and losod as sonicating proceeded. Comparing the results with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The use of ultrasound enables us to obtain well-dispersed fine zeolite A particles with the mean particle size of around 1 mm. The high solid concentration in the suspension, however, hindered the ultrasound from intense agitating, resulting in the decrease of zeolite A yield [12].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasound enables us to obtain well-dispersed fine zeolite A particles with the mean particle size of around 1 mm. The high solid concentration in the suspension, however, hindered the ultrasound from intense agitating, resulting in the decrease of zeolite A yield [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Marsh et al have demonstrated the possibility of easy, cheap and efficient production of hydroxysodalite from kaolinite by activation with sodium hydroxide solution with no prior activation of the precursor and no hydrothermal conditions [11]. Other methods of preparation were employed, such as sonochemical synthesis [12].…”
Section: Introductionmentioning
confidence: 99%
“…This sonication process may increase or change the physical and chemical properties of a material [5]. It has been studied and understood that high power ultrasonic irradiation is very effective in homogenizing the reactants in the suspension, leading to the improvement of the reactivity of both solid and liquid by simulating their active surface [6]. Purification of natural zeolite by using ultrasonic technique is also applied by researchers to remove and separate impurities materials; this technique is believed to deliver faster processing and result [7].…”
Section: Introductionmentioning
confidence: 99%